Evaluation of cholera surveillance systems in Africa: a systematic review - Mercy, Kyeng; Pokhariyal, Ganesh; Takah Fongwen, Noah; Kivuti-Bitok, Lucy (Frontiers in Epidemiology, 2024)
Introduction Despite several interventions on the control of cholera, it still remains a significant public health problem in Africa. According to the World Health Organization, 251,549 cases and 4,180 deaths (CFR: 2.9%) were reported from 19 African countries in 2023. Tools exist to enhance the surveillance of cholera but there is limited evidence on their deployment and application. There is limited evidence on the harmonization of the deployment of tools for the evaluation of cholera surveillance. We systematically reviewed available literature on the deployment of these tools in the evaluation of surveillance systems in Africa. Method Three electronic databases (PubMed, Medline and Embase) were used to search articles published in English between January 2012 to May 2023. Grey literature was also searched using Google and Google Scholar. Only articles that addressed a framework used in cholera surveillance in Africa were included. The quality of articles was assessed using the appropriate tools. Data on the use of surveillance tools and frameworks were extracted from articles for a coherent synthesis on their deployment. Result A total of 13 records (5 frameworks and 8 studies) were fit for use for this study. As per the time of the study, there were no surveillance frameworks specific for the evaluation of surveillance systems of cholera in Africa, however, five frameworks for communicable diseases and public health events could be adapted for cholera surveillance evaluation. None (0%) of the studies evaluated capacities on cross border surveillance, multisectoral one health approach and linkage of laboratory networks to surveillance systems. All (100%) studies assessed surveillance attributes even though there was no synergy in the attributes considered even among studies with similar objectives. There is therefore the need for stakeholders to harmoniously identify a spectrum of critical parameters and attributes to guide the assessment of cholera surveillance system performance.